Mashkan-shapir and the Anatomy of an Old Babylonian City - Stone, Elizabeth C. (The Biblical archaeologist, 1992)
The earliest textual references to Mashkan-shapir depict a town with humble origins. During the first quarter of the second millennium B.C.E., however, Mashkan-shapir became one of the most prominent cities in Mesopotamia because of its location at the northernmost point where the systems of the Tigris and Euphrates rivers converged sufficiently to permit navigation between them.